Use of Transcutaneous Auricular Vagus Nerve Stimulation as an Adjuvant Therapy for the Depressive Symptoms of COVID-19: A Literature Review - Guo, Zhi-Peng; Sörös, Peter; Zhang, Zhu-Qing; Yang, Ming-Hao; Liao, Dan; Liu, Chun-Hong (Frontiers in Psychiatry, 2021)
The coronavirus disease 2019 (COVID-19) comprises more than just severe acute respiratory syndrome. It also interacts with the cardiovascular, nervous, renal, and immune systems at multiple levels, increasing morbidity in patients with underlying cardiometabolic conditions and inducing myocardial injury or dysfunction. Transcutaneous auricular vagus nerve stimulation (taVNS), which is derived from auricular acupuncture, has become a popular therapy that is increasingly accessible to the general public in modern China. Here, we begin by outlining the historical background of taVNS, and then describe important links between dysfunction in proinflammatory cytokine release and related multiorgan damage in COVID-19. Furthermore, we emphasize the important relationships between proinflammatory cytokines and brain circuits. Finally, we discuss how taVNS improves immune function via the cholinergic anti-inflammatory pathway and modulates brain circuits via the hypothalamic–pituitary–adrenal axis, making taVNS an important treatment for post-COVID-19 sequelae. Our review suggests that the link between anti-inflammatory processes and brain circuits could be a potential target for treating COVID-19-related multiorgan damage, as well as mental disorders using taVNS